2016
DOI: 10.1093/geront/gnw004
|View full text |Cite
|
Sign up to set email alerts
|

Elder Abuse: Global Situation, Risk Factors, and Prevention Strategies

Abstract: The findings highlight a growing consensus across studies regarding the extent and causes of elder mistreatment, as well as the urgent need for efforts to make elder mistreatment prevention programs more effective and evidence based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
559
7
73

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 542 publications
(665 citation statements)
references
References 64 publications
26
559
7
73
Order By: Relevance
“…Most international studies found women are more likely than men to experience elder abuse. 10 Several theories may explain the possible causes of elder abuse by family members. 11 According to the social exchange theory, elder abuse may arise because of older people's dependence on the family members, while situational theory focuses on the role of stress and the burden of caregiving as precursors to elder abuse.…”
Section: -6 Eldermentioning
confidence: 99%
“…Most international studies found women are more likely than men to experience elder abuse. 10 Several theories may explain the possible causes of elder abuse by family members. 11 According to the social exchange theory, elder abuse may arise because of older people's dependence on the family members, while situational theory focuses on the role of stress and the burden of caregiving as precursors to elder abuse.…”
Section: -6 Eldermentioning
confidence: 99%
“…In fact, mistreatment of the elder nursing home care recipients has rarely been tackled even on a global scale (17,18). One recent prospective study from Hong Kong (19) suggests that abusive behaviour of caregivers toward Chinese elderly with dementia is associated with the symptoms of burnout.…”
mentioning
confidence: 99%
“…A 2009 review study of the published literature shocked the field by concluding that there was not sufficient evidence to attest to the effectiveness of any elder abuse prevention intervention (Ploeg, Fear, Hutchison, MacMilllan, & Bolan, 2009). More shocking (and perhaps more discouraging), this same conclusion was confirmed seven years later in a 2016 study (Pillemer, Burnes, Riffin, & Lachs, 2016).…”
Section: Why Evaluate?mentioning
confidence: 79%